Pengaruh Kompensasi, Motivasi Kerja Terhadap Kepuasan Kerja Karyawan Pasca Pandemi Covid-19 - diah, Halimatusa’; Fauzi, Achmad; Putri Aprillia, Dwi; Dwi Handoko, Fajar; Nabila, Nada; Dwi Anjani, Nawang (Jurnal Ilmu Multidisiplin, 2023)
This research journal explains the attachment of work compensation and work motivation to employee job satisfaction during the Covid 19 pandemic. Our group research aims to determine whether there is an effect of work compensation & work motivation on employee job satisfaction, then the effect of compensation on employee job satisfaction, and the effect of motivation work on employee job satisfaction, and the effect of compensation & work motivation on employee job satisfaction partially and to see the effect of job compensation & work motivation on employee job satisfaction simultaneously and for simultaneous effects. this data collection using literature review.